2015
DOI: 10.1115/1.4030099
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Ingestion in the Rotor–Stator Disk Cavity of a Subscale Axial Turbine Stage

Abstract: This paper describes experiments in a subscale axial turbine stage equipped with an axially overlapping radial-clearance seal at the disk cavity rim and a labyrinth seal radially inboard which divides the disk cavity into a rim cavity and an inner cavity. An orifice model of the rim seal is presented; values of ingestion and egress discharge coefficients based on the model and experimental data are reported for a range of cavity purge flow rate. In the experiments, time-averaged pressure distribution was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The double seals shown by Sangan et al [11] also had a "buffer cavity," which was similar to the rim seal in this paper and had higher values of C c of 0.86 and 1.54. A review of ingress by Scobie et al [29] used the data of Johnson et al [27] and Balasubramanian et al [30] to derive a value of C c of 0.66 and 0.14, respectively, for the same radial overlap rim seal. Although the seal studied in this paper was a hybrid between a single radial overlap and a double radial overlap seal, the ratio of discharge coefficients for location B compared most closely to the single radial overlap seal (C c ¼ 1:32) or the data in the buffer cavity in the double seal (C c ¼ 0:86) [11,21].…”
Section: Comparison Of Configurations 1 Andmentioning
confidence: 99%
“…The double seals shown by Sangan et al [11] also had a "buffer cavity," which was similar to the rim seal in this paper and had higher values of C c of 0.86 and 1.54. A review of ingress by Scobie et al [29] used the data of Johnson et al [27] and Balasubramanian et al [30] to derive a value of C c of 0.66 and 0.14, respectively, for the same radial overlap rim seal. Although the seal studied in this paper was a hybrid between a single radial overlap and a double radial overlap seal, the ratio of discharge coefficients for location B compared most closely to the single radial overlap seal (C c ¼ 1:32) or the data in the buffer cavity in the double seal (C c ¼ 0:86) [11,21].…”
Section: Comparison Of Configurations 1 Andmentioning
confidence: 99%
“…Owen [11,12] indicated that there were three kinds of hot gas ingestions according to their origins, the externally induced (EI) ingress, the rotationally induced (RI) ingress, and the combined ingress (CI). This method of classification was widely used by the following researchers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Balasubramanian et al [11] measured time-averaged static pressure distribution and ingestion of main gas into the disk cavity of a subscale single-stage axial turbine equipped with an axially overlapping radial-clearance seal at the disk cavity rim and a labyrinth seal radially inboard. Their objective was to estimate the empirical discharge coefficients, based on an orifice model, over a range of purge flow rates.…”
Section: Introductionmentioning
confidence: 99%